Epidemiology of episodic adenolymphangitis: a longitudinal prospective surveillance among a rural community endemic for bancroftian filariasis in coastal Orissa, India - Dhal Kalpataru; Nayak Abhay N; Babu Bontha V (BMC, 2005)
Abstract Background The epidemiological knowledge on acute condition of lymphatic filariasis is essential to understand the burden and issues on management of the disease. Methods A one year long longitudinal prospective surveillance of acute adenolymphangitis (ADL) was carried out in rural population of Orissa, India. Results The annual incidence of ADL per 1000 individuals is 85.0, and is slightly higher (P > 0.05) in male (92.0) than in female (77.6). A steady rise in the incidence of ADL episodes along with the age is recorded. The distribution indicates that persons with chronic disease are more prone to ADL attacks. The average number of episodes per year is 1.57 (1.15 SD) per affected person, and is gender dependent. Duration of the episode varies from 1 to 11 days with mean duration of 3.93 (1.94 SD) days. The chronic disease is the significant predictor for the duration of the episode. The data show that fever and swelling at inguinal regions are most common symptoms. Conclusion The incidence, frequency and duration of ADL episodes in this community are similar to that of other endemic areas. As the loss due to these ADL episodes is substantial, it should be considered while further estimating the burden due to lymphatic filariasis. The disability and loss caused by chronic forms of filariasis is higher, and the additional incapacity caused by the ADL episode, majority of which occur among chronic filariasis patients, further poses the burden on individuals and their families. Hence, morbidity management measures to prevent ADL episodes among endemic communities are to be implemented.